Exploring Unique Local Cultural Values: Strategies for Utilizing Tourism Potential - Suwarti Suwarti; Aurilia Triani Aryaningtyas; Tiara Sanika L. Putriningsih; Flores Harliesyahputra Laia (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
Penadaran Village in Grobogan Regency, Central Java, Indonesia, possesses a unique and vibrant cultural heritage that remains largely untapped for tourism development. This research aimed to identify the distinctive local cultural values of Penadaran, analyze their potential for tourism, and formulate strategies for sustainable cultural tourism while preserving local wisdom. Employing a qualitative approach involving observations, interviews, and document analysis, the study engaged local community leaders, policymakers, and tourism stakeholders. The findings revealed Penadaran's rich traditions, such as the "Kirab Budaya" festival, Javanese arts, historic sites, and interfaith harmony, as the village's unique cultural assets. Based on these assets, the research identified potential for cultural tourism, religious tourism, educational tourism, and eco-tourism. Strategies were then developed for harnessing this potential through community involvement, empowerment of local resources, cultural conservation and promotion, multi-stakeholder collaborations, and sustainable planning and management. The novelty of this research lies in its specific focus on Penadaran and its efforts to formulate a comprehensive, culturally sensitive approach to sustainable tourism development. The findings contribute to the growing discourse on cultural heritage preservation and responsible tourism, offering practical insights for Penadaran and similar areas seeking to optimize their cultural tourism potential while safeguarding local traditions.